2019
DOI: 10.1161/strokeaha.119.024946
|View full text |Cite
|
Sign up to set email alerts
|

Acute Diffusivity Biomarkers for Prediction of Motor and Language Outcome in Mild-to-Severe Stroke Patients

Abstract: Background and Purpose— Early severity of stroke symptoms—especially in mild-to-severe stroke patients—are imperfect predictors of long-term motor and aphasia outcome. Motor function and language processing heavily rely on the preservation of important white matter fasciculi in the brain. Axial diffusivity (AD) from the diffusion tensor imaging model has repeatedly shown to accurately reflect acute axonal damage and is thus optimal to probe the integrity of important white matter bundles and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…The findings show that children with better cognitive ability have a better prognosis for language development. The results support the concept insisting that issues in comprehension are correlated with the most severe language disorders (49,50) . From the list of continuous variables the hearing or visual impairments showed small significant effect, possibly due to different aiding methods used in therapy process.…”
Section: Analysis Of Determinant Variables That Influence the Aac Outcome In Cp Patientssupporting
confidence: 84%
“…The findings show that children with better cognitive ability have a better prognosis for language development. The results support the concept insisting that issues in comprehension are correlated with the most severe language disorders (49,50) . From the list of continuous variables the hearing or visual impairments showed small significant effect, possibly due to different aiding methods used in therapy process.…”
Section: Analysis Of Determinant Variables That Influence the Aac Outcome In Cp Patientssupporting
confidence: 84%
“…AD, on the other hand, is a measure of water diffusion parallel to the axonal course and has been related to axonal status (Alexander et al, 2007 ). Decreased AD has been related to acute axonal damage (Song et al, 2003 ) and has been shown to predict aphasia and motor outcome 3 months post-stroke (Moulton et al, 2019 ). Moreover, AD increases have also been related to axonal damage (Arfanakis et al, 2002 ), as has been shown in the study of Kraus et al ( 2007 ) who examined the white matter in chronic traumatic brain injury (TBI) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous speech ability, one of the language functions, is most closely related to UE motor status, which explained 51% of the variance in the motor deficit and 42% in motor function, respectively (see Figures 3(c) and 3(d) ). Previous studies have mentioned that the recovery of motor and language function is operated in parallel [ 20 23 ]. Due to the lack of data demonstrating UE motor status associated with language function, current stroke rehabilitation evaluations and therapies have treated these two symptoms separately [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%